1999
DOI: 10.1007/s002280050664
|View full text |Cite
|
Sign up to set email alerts
|

Delivery outcome after the use of antidepressants in early pregnancy

Abstract: Based on this database, the use of antidepressants in early pregnancy does not seem to carry any significant risk for the infant that is detectable during the newborn period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
3
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(140 citation statements)
references
References 9 publications
5
130
3
2
Order By: Relevance
“…The risk of congenital malformations, large for gestational age, and respiratory problems was higher after exposure to TCAs than after exposure to SSRIs or other antidepressants. 8,25,26 It is possible that TCAs may have different pharmacokinetic properties than SSRIs and thereby have an effect on asthma. Uncontrolled confounding is another possible explanation.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of congenital malformations, large for gestational age, and respiratory problems was higher after exposure to TCAs than after exposure to SSRIs or other antidepressants. 8,25,26 It is possible that TCAs may have different pharmacokinetic properties than SSRIs and thereby have an effect on asthma. Uncontrolled confounding is another possible explanation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported an increased risk for preterm birth with in utero exposure to antidepressants (9)(10)(11)(12)(13)(14). Our group recently found that prenatal antidepressant use, independent of depression, was associated with a lower gestational age and an increased risk of prematurity (15).…”
Section: Introductionmentioning
confidence: 99%
“…In a long-term study on mothers who took fluoxetine during pregnancy and on their total of 55 infants, no difference in the overall intelligence and language development of the infants and the control group, nor in their temperaments, moods, arousal states, activity levels, distractibility, and behavioral problems, was observed [17]. According to the Swedish National Registry data [18], the intake of paroxetine during the first gestational period increases the risk of the infant developing congenital heart abnormality, so it is not recommended for use during pregnancy. Sertraline has been reported as not having increased the risk of congenital abnormality, miscarriage, and still birth [18,19].…”
Section: Drug Treatment During Pregnancymentioning
confidence: 97%
“…According to the Swedish National Registry data [18], the intake of paroxetine during the first gestational period increases the risk of the infant developing congenital heart abnormality, so it is not recommended for use during pregnancy. Sertraline has been reported as not having increased the risk of congenital abnormality, miscarriage, and still birth [18,19]. Fluvoxamine and citalopram are Category C drugs.…”
Section: Drug Treatment During Pregnancymentioning
confidence: 99%